Sistem Pendukung Keputusan Seleksi Pemberian Uang Kuliah Tunggal Menerapkan Metode WASPAS - Tri Hasanah Bimastari Aviani; Asep Toyib Hidayat (Universitas Budi Darma, 2020)
Uang Kuliah Tunggal (UKT) is a system that is applied in the financing of the lectures to be borne by the students of the State Universities which are under the Ministry of Research, Technology and Higher Education (Kemenristek Dikti). Single tuition consists of seven groups, namely groups UKT 1 (one), the group of UKT 2 (two), a group of UKT 3 (three), the group of UKT 4 (four), the group of UKT 5 (five), the group of UKT 6 (six) and group 7 (seven), which nominal varies. In determining the provision of Single tuition fee (UKT) needed a System Supporting the Decision. In the determination of decisions, often appear subjective assessment of the decision makers, this can be an obstacle in the selection process because the results obtained are not the maximum. For it in build a system supporting the decision to utilize a method that is WASPAS. Methods WASPAS can be used to select the Student recipient of the Uang Kuliah Tunggal (UKT) criteria-the criteria that have been determined. The results obtained from this study is that there is one student with the highest value 10,88 ranked one, thus the student is entitled to receive a Uang Kuliah Tunggal (UKT)